Influence of preparation conditions on the structure of MCM-41 and catalytic performance of Ru/MCM-41 in benzene hydrogenation. (1st February 2014) - Liao, Hongguang; Ouyang, Donghong; Zhang, Jing; Xiao, Yanjuan; Liu, Pingle; Hao, Fang; You, Kuiyi; Luo, He'an
The influence of the preparation conditions on the structures of mesoporous molecular sieve MCM-41 were studied. The prepared MCM-41 samples were characterised by nitrogen physical adsorption–desorption, powder X-ray diffraction, transmission electron microscopy, FT-IR spectroscopy, thermo gravimetric analysis, differential scanning calorimetry and water/benzene static adsorption technologies. Ru/MCM-41 catalysts were then prepared by double solvent impregnation method and tested for benzene hydrogenation to cyclohexene. The structure characteristics of MCM-41 have a great effect on cyclohexene selectivity in benzene hydrogenation process. Ruthenium supported on MCM-41 with moderate surface area, larger pore size and pore volume, better long-range-order of hexagonal mesoporous shows better catalytic performance for benzene hydrogenation to cyclohexene.